Konstruksi Wacana Moral Dalam Putru Pasaji - Anak Agung Inten Mayuni; Ida Bagus Gde Yudha Triguna; Nanang Sutrisno (Kamaya: Jurnal Ilmu Agama, 2020)
Putru Pasaji keeps a wealth of knowledge and wisdom of the archipelago's ancestors, especially regarding Hindu eschatology. The eschatological discourse in this text interrelates with other discourses, including morality. The construction of moral discourse in Putru Pasaji is studied using discourse theory with a constructivist approach. Moral discourse has an important position in Putru Pasaji because it is related to the pitara's life after death. Heaven and hell are determined by the results of the actions and the moral quality of the pitara during his lifetime. The moral teachings in Shiva-Buddha construct moral discourse in its eschatological interrelations in a holistic and integral manner